2021
DOI: 10.1021/acsbiomaterials.0c01324
|View full text |Cite
|
Sign up to set email alerts
|

Structural Evaluation of the Choline and Geranic Acid/Water Complex by SAXS and NMR Analyses

Abstract: Recently, choline and geranic acid (CAGE), an ionic liquid (IL), has been recognized to be a superior biocompatible material for oral and transdermal drug delivery systems (DDS). When CAGE is administered, CAGE would be exposed to various types of physiological fluids, such as intestinal and intradermal fluids. However, the effect of physiological fluids on the structure of CAGE remains unclear. In the present study, molecular structures of CAGE with different ratios of water were investigated using small-angl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 41 publications
3
29
1
Order By: Relevance
“…In addition, water-mediated H-bonding interactions with CAGE ILs and hydrophilic part ethanol are helpful to the various structural formations. The earlier report suggests that the structure of CAGE ILs transitioned from lamellar phase to micellar phase at more than 67 vol % of water [ 61 ]. Similarly, we also found that micellar formations are more favorable for the stabilization of the insulin dimer.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, water-mediated H-bonding interactions with CAGE ILs and hydrophilic part ethanol are helpful to the various structural formations. The earlier report suggests that the structure of CAGE ILs transitioned from lamellar phase to micellar phase at more than 67 vol % of water [ 61 ]. Similarly, we also found that micellar formations are more favorable for the stabilization of the insulin dimer.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is conrmed that CAGE maintains its structure with water up to 17 vol% and this information is useful to understand the drug delivery applications of CAGE. 15 Recently, surface tension and thermal expansion coefficients of various aqueous solutions of CAGE have been investigated, providing a new perspective on CAGE behavior; the liquidvapor interface, and its mechanism in a sophisticated way. This will inspire scientists to explore other applications of CAGE and related materials.…”
Section: Interaction Of Cage With Body Fluidsmentioning
confidence: 99%
“…The most effective 1 : 2 ratio of CAGE has a viscosity 569 AE 19 mPa s, conductivity 13.79 AE 0.28 mS m À1 with diffusion coefficient 2.2 Â 10 À12 m 2 s À1 . 6 Moreover, CAGE has a molecular weight 440.32 g mL À1 with a density 0.989 : 0.001 g mL À1 at 25 C. 15,16…”
Section: Synthesis Of Cagementioning
confidence: 99%
“…Moreover, the internal structure of ILs may alter when exposed to body fluid or water dilution. Taking CAGE as an example, a 25–50 vol% of water would transfer ILs into the lamellar phase, while further dilution would lead to micelle formation via aggregation of geranate anions’ hydrophobic chains [ 78 ]. However, current research works seldom discuss the influence of hydration state on the permeation enhancement of ILs.…”
Section: Novel Pharmaceutical Strategies For Skin Penetrationmentioning
confidence: 99%